The Impact of Effleurage Technique Massage on Blood Pressure toward Elderly Hypertension in Peguyangan Village - Ni Luh Seri Astuti; I Nyoman Dharma Wisnawa; I Gede Satria Astawa (KHD-Production, 2022)
Background: One of the vulnerable groups is elderly. Entering the aging process, the elderly will have a decrease a physiological disfunction which make some of non-spreadable disease appear such as hypertension. In this critical situation, a solution is needed to tackling hypertension. One of the non-pharmacological therapy that can be handle for hypertension is effleurage massage. Aim: The aim of this study is to determine the effect of effleurage technique massage on blood pressure toward elderly hypertension at Peguyangan Village. Method: This study is use a quantitative method with quasy experimental design which research design of pre-post-test control design. Sample of this study were 15 respondents in every group. This massage therapy using effleurage massage technique during 20 minutes while control group rest for 20 minutes. Technique sample is using a purposive sampling. Data analysis with Wilcoxon Rank Test with Significance level α <0,05 from the result in the treatment group shows that the p value (sig). Conclusion: The massage of effleurage technique for 20 minutes affects toward lowering blood pressure in the elderly hypertension but resting for 20 minutes has not significantly on the reducing of hypertension blood pressure in elderly.